Phosphorus supplying capacities of soils previously fertilized with different rates of P - Yli-Halla, Markku (Agricultural and Food Science, 1991)
The residual effect of repeated P fertilizer applications was studied in a material of 30 silty clay soil samples collected from an 11-year field experiment in which a total of 0, 154, 309, 541 or 696 kg P/ha had been applied in annual doses. Half of the experiment had been limed twice with CaCO3 (10 tons/ha). In a pot experiment, six yields of Italian ryegrass were grown in soils taken from each plot, and the P uptake by the grass was determined. Soil P was extracted with water (Pw) and 0.5 M ammonium acetate-0.5 M acetic acid at pH 4.65 (PAAAC)- Reversibly adsorbed P (Pi) was extracted by a new method in which P desorbing from the soil was collected in strips of filter paper impregnated with iron hydroxide. P uptake by pot-grown grass from soils fertilized with increasing rates of P in the field corresponded to 30, 72, 100 and 112 kg larger quantities of P per hectare, compared to the soil not receiving P in the field experiment. The apparent utilization of residual fertilizer P ranged from 16 % to 25 %. The reserve of potentially desorbable P in soil had been affected much more by the fertilizer applications than had P uptake by crops in the field. The ability of the three extraction methods (Pw, Pi, PAAAC) to predict P uptake by pot-grown ryegrass was discussed. The Pi method appeared to be well suited for assessment of potentially available P reserves both in limed and unlimed soils.